Adenosine-A2A Receptor Signaling Plays a Crucial Role in Sudden Unexpected Death in Epilepsy - Shen, Hai-Ying; Baer, Sadie B.; Gesese, Raey; Cook, John M.; Weltha, Landen; Coffman, Shayla Q.; Wu, Jie; Chen, Jiang-Fan; Gao, Ming; Ji, Teng (Frontiers in Pharmacology, 2022)
Adenosinergic activities are suggested to participate in SUDEP pathophysiology; this study aimed to evaluate the adenosine hypothesis of SUDEP and specifically the role of adenosine A2A receptor (A2AR) in the development of a SUDEP mouse model with relevant clinical features. Using a combined paradigm of intrahippocampal and intraperitoneal administration of kainic acid (KA), we developed a boosted-KA model of SUDEP in genetically modified adenosine kinase (ADK) knockdown (Adk+/-) mice, which has reduced ADK in the brain. Seizure activity was monitored using video-EEG methods, and in vivo recording of local field potential (LFP) was used to evaluate neuronal activity within the nucleus tractus solitarius (NTS). Our boosted-KA model of SUDEP was characterized by a delayed, postictal sudden death in epileptic mice. We demonstrated a higher incidence of SUDEP in Adk+/- mice (34.8%) vs. WTs (8.0%), and the ADK inhibitor, 5-Iodotubercidin, further increased SUDEP in Adk+/- mice (46.7%). We revealed that the NTS level of ADK was significantly increased in epileptic WTs, but not in epileptic Adk+/- mutants, while the A2AR level in NTS was increased in epileptic (WT and Adk+/-) mice vs. non-epileptic controls. The A2AR antagonist, SCH58261, significantly reduced SUDEP events in Adk+/- mice. LFP data showed that SCH58261 partially restored KA injection-induced suppression of gamma oscillation in the NTS of epileptic WT mice, whereas SCH58261 increased theta and beta oscillations in Adk+/- mutants after KA injection, albeit with no change in gamma oscillations. These LFP findings suggest that SCH58261 and KA induced changes in local neuronal activities in the NTS of epileptic mice. We revealed a crucial role for NTS A2AR in SUDEP pathophysiology suggesting A2AR as a potential therapeutic target for SUDEP risk prevention.